Improving students' spiritual intelligence through ISMUBA teacher competencies - Yusutria, Yusutria; Yuherman, Yuherman; Hopid, Abdul; Sutipyo, Sutipyo R; Febriana, Rina; Hudatun, Egi Nur; Muharrom, Ahmad Syafiq; Kurniannur, Nimas Wening; Oktavianda, Tira; Firdausyah, Amadatur (Empathy : Jurnal Fakultas Psikologi, 2024)
The problem of the immoral decline of the younger generation is not something that should be kept secret any longer. So, a solution is needed to overcome these problems to shape the nation's character, which significantly influences the quality of morals and religious intelligence, which is not only intellectually intelligent but also emotionally and spiritually intelligent. Increasing students' spiritual intelligence through the competence of ISMUBA teachers is necessary and an attractive solution to achieving learning and educational goals. This research seeks to explore the competence of ISMUBA teachers and the supporting and inhibiting factors in increasing spiritual intelligence. This research uses a qualitative-descriptive method. The results of a study on growing students' spiritual intelligence through the competence of ISMUBA teachers by using an interactive learning approach, getting used to worship and doing good deeds, and providing examples and habits. The internal supporting factors stem from students' high self-awareness, so they automatically carry out religious practices that can increase their spiritual intelligence. External factors include the role of teachers as motivators, mentors, and directors and the role of parents as supporters as well as advisors, directors, and motivators of children. The inhibiting factor is a low level of self-awareness, which causes laziness and a lack of enthusiasm to carry out activities that can increase spiritual intelligence. Meanwhile, external obstacles are family conditions and the influence of the surrounding environment.